Podridão floral dos citros: controle preventivo mediante fungicidas, biorreguladores e fertilizantes químicos - Mendonça, Laís Barbosa Prazeres [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The postbloom fruit drop (PFD), caused by Colletotrichum acutatum and C. gloeosporioides, considerably reduces citrus production in the main producing areas and the use of fungicides is still the most effective control strategy. In 2012 benzimidazoles, chemical group which, for many years, was important in controlling PFD, have had their use suspended in citrus orchards for the production of exportation juice, an adaptation requirement to the quality standards of the USA, the main buyer. As a result, it was made necessary to search for new fungicides enhancing good agronomic efficiency and heeding the rate of waste allowed. Thus, the aim of this study was to evaluate new chemical groups of fungicides, alone or in combination, as well as growth regulators, resistance inducers and chemical fertilizers to control PFC in commercial orchards, during 2012/13 and 2013/14 crop seasons. The experiments were performed with sweet orange 'Pera' trees located in the municipalities of Itapetininga (IT), Santa Cruz do Rio Pardo (SC) and Casa Branca (CB). The experimental design was a randomized block design (RBD) with five replications. Among the new management strategies were evaluated: i) fungicides of the strobilurin group in combination with other chemical groups; ii) growth regulators applied alone or in combination with hormonal regulators and fungicides; iii) efficiency of strobilurin and triazole mixtures applied in conjunction with hormonal regulators and chemical fertilizers; iv) efficiency of strobilurins and triazoles combined with chlorothalonil, v) efficiency Stimulate® combined to Hold® and fungicide. It was observed that fungicides of the strobilurin and triazoles groups or in combination with chlorothalonil, as well as the use of bioregulators e resistance inducers are efficient alternative preventive control of the PFC

A Podridão floral dos citros (PFC), ocasionada por Colletotrichum acutatum e C. gloeosporioides, reduz consideravelmente a produção de citros nas principais áreas produtoras e a utilização de fungicidas ainda é a estratégia de controle mais eficaz. No ano de 2012 os benzimidazóis, grupo químico que por muitos anos foi importante no controle de PFC, tiveram seu uso suspenso em pomares de citros destinados à produção de suco para exportação, uma exigência de adequação aos padrões de qualidade dos EUA, principal comprador. Em decorrência disso, fez-se necessária a busca por novos fungicidas, que apresentassem boa eficiência agronômica e que atendessem às taxas de resíduos permitidas. Sendo assim, o objetivo do presente estudo foi avaliar novos grupos químicos de fungicidas, isoladamente ou em combinação, bem como reguladores de crescimento, indutores de resistência e fertilizantes químicos no controle da PFC, em pomares comerciais, nas safras 2012/13 e 2013/14. Os experimentos foram realizados em plantas de laranjeira „Pera‟ localizadas nos municípios paulistas de Itapetininga (IT), Santa Cruz do Rio Pardo (SC) e Casa Branca (CB). O delineamento experimental utilizado foi o de blocos casualizados (DBC), com cinco repetições. Dentre as novas estratégias de manejo foram avaliadas: i) Fungicidas dos grupos das estrobilurinas em combinação com outros grupos químicos; ii) Reguladores de crescimento aplicados isoladamente ou em combinação com reguladores hormonais e fungicidas; iii) Eficiência de misturas de estrobilurinas e triazóis, aplicadas em conjunto com reguladores hormonais e fertilizantes químicos; iv) Eficiência de clorotalonil combinado a estrobilurinas e triazóis, e v) Eficiência de Stimulate combinado a Hold e fungicida. Observou-se que fungicidas do grupo das estrobilurinas em combinação com triazóis ou clorotalonil, bem como a utilização de biorreguladores e indutores ...
Keywords: Cítricos - Doenças e pragas - Controle; Fungicidas; Colletotrichum gloeosporioides; Adubos e fertilizantes; Reguladores de crescimento; Agricultural chemicals